STUDI PEMBELAJARAN RUMAH QURANI DALAM MENINGKATKAN KEMAMPUAN BERBAHASA ANAK USIA DINI DI RA ASSAKINAH SEJAHTERA KAB. BANDUNG BARAT - Heryanto Heryanto (IKIP Siliwangi Bandung, 2014)
This research was motivated by the problems in early childhood language skills in RA Assakinah Sejahtera, namely the tendency of interest in learning language skills, especially speaking skills are still relatively low and there is still the teacher’s ability or competence is not optimal. So, we need a model of learning that is more effective in the learning process. The approach used in this study is a qualitative descriptive approach using the techniques of observation data collection, interviews, documentary studies, and literature studies.This study aimed to describe: 1) the learning objective of quranic home conditions in RA Assakinah Sejahtera, 2) implementation of the quranic home method in RA Assakinah Sejahtera in order to improve language skills, 3) the results achieved from the use of the quranic home method, and 4) using barriers of quranic home method. The theoretical basis of this study, researchers refer to several concepts: 1) learning theory, Law 20 of 2003 on National Education System chapter 1, verse 2002, 2) The concept of Quranic home learning, pusdiklatrumahqurani 2012, 3) The concept of early childhood education, curriculum 2004 of kindergarten and Raudlatul Afhtal (Depdiknas, 2004: 2), and 4) Language Concepts, Strategies Mastery Speak, Suwarna 2002.The results of this study indicate that in improving language skills for early childhood needed teacher guidance and parents collaboration. Guidance by the teacher implemented is designed to be more flexible in the sense of a child can learn with class organization that vary in individual activities, classical, and groups. Cooperation with the parents conducted to establish communication through the development of children's ability liaison books are competitors by providing stimulation reward as maintaining cooperative school with his parents. Conclusions from this research is the Quranic home learning can improve language skills in early childhood in RA Assakinah Sejahtera and in delivering learning material formulated with a variety of themes that can applied with other lessons or other themes.